Sikkim State Annual Plan 2000-2001 - Planning Commission (Planning Commission, 2000)
The Ninth Five Year Plan has been conceived for achieving a significant leap forward for the State in terms of improvement in the living standards and ensuring equitable distribution of gains from the economic development processes including creation of employment opportunities for its people. The broad strategy which is to be followed during the Ninth Five Year Plan has been detailed in the main document containing the proposals for the State during the period 1997- 2002. The State would be aiming at a growth rate of 100% per annum by stepping up the quantum of investment, improvement in efficiency with which capital is being utilized, achieving self reliance and self sufficiency in the various sectors, improvement of productivity and improving the efficiency in utilization of human and capital resources.
Planning and Development Department Government of Sikkim Gangtok